The Upper Cretaceous ophiolites and magmatic arc rocks in the Eastern Taurus, Turkey - Beyarslan, M (Springer India, 2005)
The Eastern Taurus extends from Elbistan to the Iran/Iraq frontier in Eastern Turkey, bounded by the Southeast Thrust Zone to the South. Younger sedimentary and volcanic units discordantly overlie the Palaeozoic-Mesozoic rocks to the north. The Palaeozoic-Mesozoic metamorphic rocks consists of poly-metamorphic gneisses, amphibolites, marbles and schists. The metamorphic units were thrusted onto the ophiolites or the Maden Complex, which is interpreted as continental fragments that have rifted from Gondwana in the Triassic in conjunction with the opening of a southerly Neotethyan ocean basin. Upper Cretaceous magmatic rocks are composed of ophiolites associated with arc-related magmatics. Isolated ophiolite outcrops are generally composed of dunites, pyroxenites, gabbros, dyke swarms and pillow lavas. Unusually, the Guleman ophiolite consists of harzburgitic and dunitic tectonites. The crystallization sequence of gabbros in the Eastern Taurus ophiolites suggests that these ophiolites were formed in a SSZ type setting. Arc-related magmatic rocks include basaltic pillow lavas, andesitic lava flows pyroclastics and granitic intrusions. Field, petrographical and geochemical data also suggest that these magmatic rocks were formed in a supra-subduction zone. The ophiolites are derived from an oceanic crust in the upper plate of a subduction zone. The Upper Cretaceous arc-related magmatic rocks developed on this oceanic lithosphere.
Keywords: ophiolites; basic volcanics; igneous stratigraphy; tectonic evolution; Eastern Taurus; Turkey